Drought Impacts on Tree Root Traits Are Linked to Their Decomposability and Net Carbon Release - Carrillo, Yolima; Tissue, David T.; Bruna, Sophia; Maier, Chelsea; Dijkstra, Feike A. (Frontiers in Forests and Global Change, 2022)
Root trait plasticity can facilitate plant adjustment to water shortages, but the impact of altered traits on belowground carbon (C) cycling is mostly unknown. While drought and nutrient availability can alter root morphological and chemical traits that may affect root decomposition, direct assessments of drought mediated changes on decomposability are not available. We exposed four tree species contrasting in drought stress tolerance and root traits to three dry-down and recovery periods (over 5 months after 11 months of growth in well-watered conditions) under high and low nutrient conditions. We then assessed early stage root decomposability in relation to their morphology and chemistry as well as implications for CO2 release when accounting for effects on root biomass. While each species showed a unique set of responses, drought generally reduced root diameter and increased nitrogen concentration. We found limited evidence that morphological responses to drought were counteracted by high nutrient supply. Results indicated that the degree of association between morphological and nutrient root trait responses to drought and decomposability varied with different species. However, across these contrasting woody species, drought-induced increases in nitrogen and phosphorus concentrations were associated with drought-induced increases in early stage root decomposability. When accounting for changes in root biomass, estimated overall C loss through root decomposition increased with drought stress. Our experimental results demonstrate that changes in tree root traits with drought can enhance C loss via root decomposition, and with other factors being equal, drought may potentially contribute to a positive feedback to climate change. Our findings contribute empirical evidence to help disentangle the multiple factors involved in root contribution to C balances at the ecosystem level.